2022
DOI: 10.33714/masteb.1041493
|View full text |Cite
|
Sign up to set email alerts
|

Black Soldier Fly (Hermetia illucens) Larvae as an Ecological, Immune Booster and Economical Feedstuff for Aquaculture

Abstract: Black soldier fly larva can renovate biological trashes into valuable nutrients, for instance, proteins, lipids, and chitin, which decrease ecological encumbrance happening due to organic wastes accumulation. Even though rapid demand for proteinaceous food is predictable, insects got less attention in the animal feed business primarily due to technical and monetary hurdles. Moreover, many times research highlighted the consumer and producer preferences for insects' meal potential in livestock feeding. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…The feed intake and feed costs were significantly higher for the CN diet than the other diets, and consequently, the economic feed conversion ratio of the CN diet was also the highest causing a higher break-even yield. This study confirms that the use of BSFL and CN as alternative sources of protein increases the profitability of fish farming, which concurs with the results of other studies that worked with fish (Mugo-Bundi et al, 2015;Ngugi et al, 2016;Onsongo et al, 2018;Chia, 2019;Shit, 2021;Wachira et al, 2021;Çetingül and Shah, 2022;Limbu et al, 2022). Interestingly, it has further been demonstrated that utilization of CN can effectively substitute up to 75% of fish meal without compromising growth performance, survival, nutrient utilization and economic benefits, however, when substitution was as high as 100%, the performances declined (Mugo-Bundi et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…The feed intake and feed costs were significantly higher for the CN diet than the other diets, and consequently, the economic feed conversion ratio of the CN diet was also the highest causing a higher break-even yield. This study confirms that the use of BSFL and CN as alternative sources of protein increases the profitability of fish farming, which concurs with the results of other studies that worked with fish (Mugo-Bundi et al, 2015;Ngugi et al, 2016;Onsongo et al, 2018;Chia, 2019;Shit, 2021;Wachira et al, 2021;Çetingül and Shah, 2022;Limbu et al, 2022). Interestingly, it has further been demonstrated that utilization of CN can effectively substitute up to 75% of fish meal without compromising growth performance, survival, nutrient utilization and economic benefits, however, when substitution was as high as 100%, the performances declined (Mugo-Bundi et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, the farming of BSF ( Hermetia illucens ) has gained attention as a means to obtain proteins and fats for the animal feed industry while valorising both homogeneous and heterogeneous food waste that might otherwise be destined for the incinerator or landfill. Massive farms now exist worldwide, processing hundreds of tons of homogeneous waste streams [ 17 , 18 ]. The life cycle of the BSF consists of five life stages: egg, larva, pre-pupa, pupa and adult.…”
Section: Introductionmentioning
confidence: 99%